Behind the Scenes for the Designation of the Corales de Profundidad National Natural Park of Colombia - Alonso, David; Vides-Casado, Martha; Arias-Isaza, Francisco; Zambrano, Hernando; Rodriguez, Emilio; Rocha-Gutierrez, Venus; Herron, Pilar; Castillo, Anny (Frontiers in Marine Science, 2021)
1 Introduction Deep-water environments make up 64% of the world's oceans (nearly 202 million km2). In the past, the belief that this environment represented one of the most stable and unproductive ecosystems on the planet has been refuted by scientific research and the interest of potential productive sectors evaluating seabed resources. Human activities that threaten the health of deep-sea threats are uncontrolled and unregulated fishing, deep-sea mining, oil spills, marine litter, and climate change. With recent advances in technology, the study of deep-sea coral communities is a growing subject. The deep-sea corals are long-lived, slow-growing, and fragile systems, making them especially vulnerable to physical damage. In the last 40 years, Colombia has discovered these communities' existence scarcely distributed in its territorial waters. A representative and irreplaceable sample of deep-sea coral formations triggered in 2013 the establishment of the Corales de Profundidad National Natural Park, a Marine Protected Area (MPA), which holds 40 % of the marine biodiversity known in the Colombian Caribbean continental shelf-slope break. The MPA's essential ecological value is the Madracis myriaster species' presence as a primary habitat-forming organism, a unique habitat for the Caribbean and the world. Here we describe the MPA creation process in three phases. Firstly, in the provisioning phase, three main threats from human activities are identified. Secondly, in the preparation phase, the area's conservation objectives and management category are defined, and the negotiation process with the fishing, communications, and oil and gas economic sectors is described. Lastly, in the designation phase, three MPA scenario proposals were evaluated, assessing the minimum distance, the possible effects of activities in the area as the main criteria for the buffer zone and the management of possible future impacts. As a result, the most extended boundary was adopted, guaranteeing these communities' conservation despite the limited information to carry out a complete planning process. The MPA designation is considered the first experience of deep communities in the Southern Caribbean and an example that it is possible to have effective conservation agreements with economic sectors.